Bringing dark data into the light: A case study of the recovery of Northwestern Atlantic zooplankton data collected in the 1970s and 1980s. (June 2015) - Wiebe, Peter H.; Allison, M. Dickson
Abstract: Data generated as a result of publicly funded research in the USA and other countries are now required to be available in public data repositories. However, many scientific data over the past 50+ years were collected at a time when the technology for curation, storage, and dissemination were primitive or non-existent and consequently many of these datasets are not available publicly. These so-called "dark data" sets are essential to the understanding of how the ocean has changed chemically and biologically in response to the documented shifts in temperature and salinity (aka climate change). An effort is underway to bring into the light, dark data about zooplankton collected in the 1970s and 1980s as part of the cold-core and warm-core rings multidisciplinary programs and other related projects. Zooplankton biomass and euphausiid species abundance from 306 tows and related environmental data including many depth specific tows taken on 34 research cruises in the Northwest Atlantic are online and accessible from the Biological and Chemical Oceanography Data Management Office (BCO-DMO).